2017
DOI: 10.1016/j.jval.2016.09.2403
|View full text |Cite
|
Sign up to set email alerts
|

Limited Effectiveness of Diabetes Risk Assessment Tools in Seniors’ Facility Residents

Abstract: In this group of seniors with no known diabetes history, mean HbA level approximated that in the general population and neither survey effectively identified those with elevated blood glucose levels. These findings should be confirmed in a larger study; nevertheless, routine use of these surveys as a diabetes screening strategy does not appear to be warranted at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The performance of NCDRS was more effective in the ≤44 age group compared with the ≥45 age group in both DM and preDM. The previous study has shown that the DM risk assessments could neither provide efficient screening of DM, nor could they identify individuals with elevated blood glucose levels in an older population (≥55 years old) [34]. That is, like other assessments, NCDRS may be more applicable in a younger population.…”
Section: Discussionmentioning
confidence: 97%
“…The performance of NCDRS was more effective in the ≤44 age group compared with the ≥45 age group in both DM and preDM. The previous study has shown that the DM risk assessments could neither provide efficient screening of DM, nor could they identify individuals with elevated blood glucose levels in an older population (≥55 years old) [34]. That is, like other assessments, NCDRS may be more applicable in a younger population.…”
Section: Discussionmentioning
confidence: 97%